English Code-switching: An Increasing Practice in Burushaski Discourse - Abdul Saeed (University of Chitral Journal of Linguistics and Literature, 2023)
This study mainly aims to explore Burushaski speaking students’ behaviour towards English code-switching with regard to increase in their educational level. The study also aims to sort out the class of words which mostly become a source of code-switching. The data were collected from a total of 90 participants which were divided into three groups. Each group consisted of 30 participants. Group discussions between the participants in Burushaski language were held and were recorded for each group. The findings show variations in the amount of English code-switching within the conversation of each group which demonstrate that the amount of code-switching in conversation of graduation level students is greater than those of matriculation and intermediate level students respectively. Among the parts of speech, nouns were found to be highly switched in Burushaski discourse.